The importance of moral sensitivity in nursing education: A comparative study - Uncu, Fatos; Gunes, Dilek (Wiley-Hindawi, 2021)
Background/Aim: This study aims to determine the importance of the Ethics and Deontology in Nursing course in nursing education for the purpose of revealing the level of moral sensitivity of nursing students. Materials and Methods: In our research, which is a descriptive study, data were collected from 461 nursing students who studied at the Faculty of Health Sciences. In the study, the Personal Information Form and Moral Sensitivity Questionnaire (MSQ) were used as data collection forms. The findings from the study were evaluated with SPSS 22.00 package software, and the level of significance in all analyses was accepted as p < 0.05. Results: The average age of the students participating in the study was 20.83 +/- 1.55. Also, 51.8% of the students took the course Ethics and Deontology in Nursing. The total mean score of the MSQ of students was determined as 83.32 +/- 16.79. A statistically significant difference was found between the students' total scores of autonomy, benefit, holistic approach, conflict, practice, orientation, and moral sensitivity, depending on whether they took the course Ethics and Deontology in Nursing. Conclusion: It was concluded that moral sensitivity in nursing students was positively influenced by the ethical education they received.
Keywords: course of ethics and deontology in nursing; moral sensitivity; nursing students